Kontribusi Green Sukuk pada Implementasi Tujuan Pembangunan Keberlanjutan di Indonesia - Adhe Pertiwi Mareta; Febyviani Dwimutian Anggraini; Kustiyah Kustiyah; Mardhiyah Hayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main goal of the Islamic financial industry is falah, which is always involved in matters beneficial to the community. The Islamic finance beginning to emphasize broader social responsibility issues, such as environmental concerns. To maintain economic sustainability and protect the environment, the world faces two challenges in an increasingly complex global era. Sukuk generally refers to a certificate that has the same value as a portion or the entirety of assets to obtain returns and services within the ownership of specific assets and projects or special investment activities. SDGs aim to reduce the impact of damage through the emphasis on achieving it through collaboration between countries and sectors. library research Sustainable development not only prioritizes economic growth but also how economic activities can ensure the healthy and non-excessive use of natural resources to achieve optimal results. However, there are several issues that hinder its implementation. In a situation like various factors that hinder sustainable economic growth in Indonesia.